Accuracy of Single Periapical Radiography in Diagnosis of Horizontal Root Fracture - Fazlolah Soleymani Najafabadi; Mahdi Dastorani; Jalil Modaresi; Fatemeh Ezodini (Tehran University of Medical Sciences, 2012)
Background and Aims: Radiographic examination is a necessary step in diagnosis of horizontal root fracture. The purpose of this study was to determine the sensitivity and specificity of single radiograph for detection of horizontal root fracture. Materials and Methods: In this analytical-descriptive study, 30 human freshly extracted teeth were used. Using a hammer and clamp, the teeth were divided into two sections accidentally and then sections were attached together by cyanoacrylate glue. Two radiographs were taken; with and without a piece of human mandibular bone. Afterward, radiographs were analyzed by three expert dentists using a slide show device. Results: The diagnostic sensitivity and specificity of single radiograph for detection of horizontal root fracture without bone was 100%, but in radiographs of teeth with bone was 82.7% and 100%, respectively. Conclusion: Based on the results of this study, in most cases, the horizontal root fractures can be detected by a single periapical radiograph.